Right Cortical Activation During Generation of Creative Insights: An Electroencephalographic Study of Coaching - Bartolomé, Gorka; Vila, Sergi; Torrelles-Nadal, Cristina; Blanco, Eduardo (Frontiers in Education, 2022)
Coaching as a human development methodology has been demonstrating its results for more than four decades. Even so, the level of confusion about its essence, and the lack of a definitive theoretical and methodological framework have caused that the effectiveness of coaching is questioned. Although some studies on coaching using neuroimaging methods have been developed, there is no recent evidence about the brain changes in electroencephalographic activity during a coaching session. The present research aims to make a comparison by electroencephalography (EEG) measurement of three different conditions, rumination (R), directive (DC) and non-directive coaching (NDC), during problem solving and goal achievement. Our hypothesis was that the use of the meta-competencies of NDC should induce a higher activation of brain mechanisms that facilitate the insight process and therefore an improvement in creative capacity. Results showed significant changes in alpha and theta frequencies in the right temporal region, and alpha, theta and gamma in the right parietal region in the NDC condition, compared to other experimental conditions. The correct use of the meta-competencies of non-directive coaching facilitates the arise of insight and the generation of creativity processes at the brain level. Thus, the application of the methodological framework of the NDC was related, in a specific way, to the creativity and the development of human knowledge.